2011
DOI: 10.1348/026151010x519964
|View full text |Cite
|
Sign up to set email alerts
|

Young children's understanding of pretend crying: The effect of context

Abstract: Reasoning about another's pretend and real crying is related to ma'ny important social cognitive abilities (e.g., emotional understanding, appearance-reality, and theory of mind). This study investigated whether children aged 6 years and younger could distinguish between instances of pretend crying and real crying as presented in stories. Sixty-five Japanese children aged 4-6 years were given stories within two contexts (Play and Non-play). In the Play context, the protagonist of the story was pretending to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 43 publications
3
17
0
1
Order By: Relevance
“…Furthermore, they are sensitive to subtle differences in other social cues (Brey & Shutts, 2015;Over & Carpenter, 2015), and are able to differentiate real from pretend emotions (Gross & Harris, 1988;Harris et al, 1986;Misailidi, 2006;Mizokawa, 2011). Furthermore, around this age, children are developing an understanding of the psychological states underlying others" behavior -their "theory of mind" (e.g., Wellman, Cross, & Watson, 2001).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Furthermore, they are sensitive to subtle differences in other social cues (Brey & Shutts, 2015;Over & Carpenter, 2015), and are able to differentiate real from pretend emotions (Gross & Harris, 1988;Harris et al, 1986;Misailidi, 2006;Mizokawa, 2011). Furthermore, around this age, children are developing an understanding of the psychological states underlying others" behavior -their "theory of mind" (e.g., Wellman, Cross, & Watson, 2001).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The results of the chi‐square analysis comparing the three theory of mind groups in the present study indicate that the children who understood first‐order false beliefs inferred a positive meaning from teacher criticism. Because 6‐year‐olds are able to discriminate between apparent emotion and real emotion (Banerjee & Yuill, ; Harris, Donnelly, Guz, & Pitt‐Watson, ; Mizokawa, ), they may detect the hidden positive message in teacher criticism by ‘reading’ the teacher's mind in the teacher condition. In other words, the real meaning of a critical message was not congruent with its ostensible meaning.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding research on emotional expression in contexts of play, the study by Mizokawa (2011), where children were presented with picture stories in a play context and in a nonplay context, showed that 4-and 5-year-old were better at distinguishing pretend crying from real crying in a pretend play context than in a non-play context. So Mizokawa (2011) suggested that the context of pretend play facilitates children's understanding of pretend crying.…”
Section: Children's Recognition Of Emotional Expressionsmentioning
confidence: 99%
“…Regarding research on emotional expression in contexts of play, the study by Mizokawa (2011), where children were presented with picture stories in a play context and in a nonplay context, showed that 4-and 5-year-old were better at distinguishing pretend crying from real crying in a pretend play context than in a non-play context. So Mizokawa (2011) suggested that the context of pretend play facilitates children's understanding of pretend crying. Furthermore, the study by Sidera et al (2013) showed that at the age of 4, despite not mastering the distinction between internal and external emotion, most children understand the playful intentionality of emotions expressed in pretend play contexts.…”
Section: Children's Recognition Of Emotional Expressionsmentioning
confidence: 99%